ANALISIS KEMAMPUAN PEMECAHAN MASALAH SISWA SMP DENGAN SOAL-SOAL PEMODELAN - Astuti, Puji; Indaryanti, Indaryanti; Santoso, Budi; Septiana, Diana; Atika, Atika (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
The development of the PISA framework from year to year is increasingly focused on problem solving. This indicates that problem-solving ability is crucial. Considerable studies at the international level on the influence of PISA implies that the world also indirectly focuses on problem-solving abilities. The National Council of Teachers of Mathematics (NCTM) mentions five basic mathematical skills, one of which is problem solving. Mathematical modeling is one of the stages of mathematical problem solving. For that, mathematical modeling problems are chosen so that student can train problem solving ability. This study aims to describe problem solving ability of junior high school students in solving mathematical modeling problems. The result of mathematics problem solving test in grade VII students at SMP Negeri 1 Palembang has three categories, that is students with problem solving ability of mathematical well, enough, and less. The lowest occurrence of the problem solving indicator is the first indicator that is to explore and understand mathematics problems.